Strategies to reduce hospital-associated bloodstream infections in a limited resource setting: Preventing Infections in Neonates (PIN) collaborative - Ibukunoluwa C. Kalu; Melanie S. Curless; Sasheela Ponnampalavanar; Aaron M. Milstone; Azanna Ahmad Kamar (Cambridge University Press, 2023)
Abstract Background: Hospitalized neonates are at high risk for hospital-associated bloodstream infections (HA-BSI) and require locally contextualized interventions to prevent HA-BSI. Methods: The Preventing Infections in Neonates (PIN) collaborative aimed to reach a 50% decrease in neonatal HA-BSI rates for a 27-bed Level IV neonatal intensive care unit (NICU). Using quality improvement (QI) methodologies, a multidisciplinary cross-cultural collaborative implemented phased and bundled interventions from July 2017 to September 2019. Descriptive statistics and statistical process control charts were used to analyze infection rates. Results: There were 916 admissions, 19,812 patient-days, and 4264 central line days in the NICU during the project period. Monthly baseline preintervention HA-BSI median rate was 3.95/1000 patient-days and decreased to 1.73/1000 patient-days (56% change) during the bundled interventions. Quarterly HA-BSI rates also decreased from the preintervention median of 4.5/1000 patient-days to 3.3/1000 patient-days during the intervention period (IRR 0.73; 95%CI 0.39, 1.36). Staff were highly compliant with hand hygiene and environmental cleaning. Through project efforts, compliance with bundle elements increased from 25% at baseline to a peak of 97% for central line (CL) insertion checklists and from 13% to a peak of 56% for CL maintenance checklists. Conclusions: Unit-based bundled interventions can reduce neonatal HA-BSI in limited resource settings. Future studies can assess similar practices in other units and the impact of the pandemic on interventions to reduce HA-BSIs.